Buriti oil associated with the use of therapeutic ultrasound on the regenerative process of peripheral nerve injury in rats - da Fonseca, Manoel L.A.; de Carvalho, Ana Flávia M.; Ferreira, Danniel C.L.; Monte, Samylla M.; Marques, Rosemarie Brandim; Maia Filho, Antônio Luiz M. (Revista Intertox de Toxicologia, Risco Ambiental e Sociedade, 2018)
Peripheral nerve lesions are a common cause of disability and may result in loss of motor and / or sensory functions, representing a significant clinical problem with unsatisfactory treatment options. A widely studied alternative in the context of tissue regeneration are the essential oils. The objective of this study was to evaluate the efficacy of Buriti oil associated with therapeutic ultrasound in the functional recovery of rats. There were 18 male Wistar rats (250 and 300g), divided into three groups: control, submitted to ultrasound and another subjected to ultrasound associated with Buriti oil. Subsequently, the right sciatic nerve of rats suffered a controlled injury by strangling a portable device with a dead weight of 5,000g / 10 minutes. Samples were collected before treatment (control) and 24 h, 7, 14 and 21 days after sciatic nerve compression. These tests consisted of filming the gait of each animal on the bottom of the glass walkway and analyzed the IMAGE-J® program. Measurements were the lengths of the legs (left back), and the distance between the toes. It has been shown that the combination of Buriti oil with ultrasound was more effective in neuromotor regeneration of rats after axonomy compared to single ultrasound therapy.